ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI MANAJEMEN PENDIDIKAN ISLAM BERBASIS EDUCATION MANAGEMENT INFORMATION SYSTEM (EMIS) - Yusri, Ahmad Fauzi; Jumaruddin (Educational Leadership: Jurnal Manajemen Pendidikan, 2024)
This research aims to analyze the implementation of the policy of the Directorate General of Islamic Education No. 5974 Th. 2019 concerning education information management based on the Education Management Information System (EMIS). This research uses library research by conducting investigations into books, literature, notes and reports about EMIS. The research results show that there are three steps that must be taken in the EMIS policy, namely organization, interpretation, and application. EMIS-based data management has made it easier to make decisions and make policies for the progress of Islamic educational institutions. However, EMIS as a database for Islamic education for policy making has not been able to be used optimally, because the level of validity and updating of the data is still not perfect.